Influence of Heat Treatment on the Formation of Amadori Compounds in Carrots - A. Wellner; Ch. Hüttl; T. Henle (Czech Journal of Food Sciences, 2009)
The formation of Amadori products (APs) during heat treatment of carrot juice and dehydration of carrots was studied. APs were measured as the corresponding N-furoylmethyl amino acids (FMAAs) after acid hydrolysis using RP-HPLC. Commercial samples of juices contained up to 108 mg furosine/100 g protein, 18 mg FM-Ala/100g protein, 13 mg FM-Val/100 g protein and 32 mg FM-GABA/100 g protein. The concentrations in dehydrated carrots were extensively higher with up to 1553 mg furosine/100 g protein, 1144 mg FM-Ala/100 g protein, 88 mg FM-Val/100 g protein and 908 mg FM-GABA/100 g protein. Heat treatment of fresh carrot juice caused only a marginal increase of Amadori compounds. Samples contained at most 16 mg furosine/100 g protein and 19 mg FM-GABA, respectively, while FM-Ala and FM-Val were not detectabele at all. In contrast, drying of carrots led to a significant increase of FMAAs. The dehydrated samples contained up to 989 mg furosine/100 g protein, 1201 mg FM-Ala/100 g protein and 969 mg FM-GABA/100 g protein, while FM-Val was not detectable.